2023
DOI: 10.3390/cancers15123136
|View full text |Cite
|
Sign up to set email alerts
|

B7H3 Role in Reshaping Immunosuppressive Landscape in MSI and MSS Colorectal Cancer Tumours

Abstract: The study aimed to assess the expression of B7H3 concerning clinicopathological and histological parameters, including MSI/MSS status, CD-8 cells, tumour-infiltrating lymphocytes (TILs), budding, TNM scale and grading. Moreover, we analyzed the B7H3-related pathways using available online datasets and the immunological context of B7H3 expression, through the 48-cytokine screening panel of cancer tissues homogenates, immunogenic features and immune composition. The study included 158 patients diagnosed with CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Investigations on B7-H3 are generating considerable interest in cancer research, as it is a promising diagnostic and prognostic marker and a viable target for anticancer treatment [ 19 21 ]. Indeed, various clinical studies have well-established the association between B7-H3 and poor prognosis [ 10 ]. The development of immunotherapy targeting B7-H3 is rapidly evolving, with many ongoing clinical trials investigating the safety and efficacy of these therapeutic approaches in cancer patients.…”
Section: B7-h3: An Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigations on B7-H3 are generating considerable interest in cancer research, as it is a promising diagnostic and prognostic marker and a viable target for anticancer treatment [ 19 21 ]. Indeed, various clinical studies have well-established the association between B7-H3 and poor prognosis [ 10 ]. The development of immunotherapy targeting B7-H3 is rapidly evolving, with many ongoing clinical trials investigating the safety and efficacy of these therapeutic approaches in cancer patients.…”
Section: B7-h3: An Overviewmentioning
confidence: 99%
“…Clinically, a high expression of B7-H3 and the TAM density in CRC tissue were associated with reduced overall survival of patients [ 65 ]. Studies examining the immune cells infiltrating the TME revealed that the M2 phenotype was predominantly present in the TME and indicated the presence of pro-tumor growth factors and cytokines released by M2 macrophage [ 10 , 65 ]. The JAK2-STAT3 pathway could probably mediate the polarization of macrophages [ 66 ].…”
Section: B7-h3: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations